2016
DOI: 10.1111/cen.13274
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Thyroid Imaging Reporting and Data System in the prediction of malignancy in nodules with atypia and follicular lesion of undetermined significance cytologies

Abstract: TIRADS seems to be useful in predicting malignancy and planning further management in the AUS subcategory, but not quite so in the FLUS subcategory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
(117 reference statements)
1
24
3
Order By: Relevance
“…gap.kr/thyroidnodule_b3.php). 30 In our web-based scoring system, the AUCs for the subcategories of cytologic atypia and architectural atypia were 0.860 and 0.658, respectively, which are higher than those reported in the previous study. The American Thyroid Association management guidelines for thyroid nodules, 7 Korean Society of Thyroid Radiology consensus statement and recommendations, 6 and French guidelines 26 on the stratified risk of malignancy of thyroid FI GU RE 2 Performance of 2 prediction models.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…gap.kr/thyroidnodule_b3.php). 30 In our web-based scoring system, the AUCs for the subcategories of cytologic atypia and architectural atypia were 0.860 and 0.658, respectively, which are higher than those reported in the previous study. The American Thyroid Association management guidelines for thyroid nodules, 7 Korean Society of Thyroid Radiology consensus statement and recommendations, 6 and French guidelines 26 on the stratified risk of malignancy of thyroid FI GU RE 2 Performance of 2 prediction models.…”
Section: Discussioncontrasting
confidence: 67%
“…As previous literature reported that the differentiation between follicular adenoma and carcinoma using ultrasound is limited, 30,37,38 we speculate that it contributed to the relatively low AUC in architectural atypia. First, the study population was not free from selection bias, and it could not be determined whether the patients were representative of the general population.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The cystic shape and the intrathyroidal location of the focal lesion led us to perform a FNAB that resulted non-conclusive. On the other hand, we think that the lack of knowledge directing towards a parathyroid origin leads to a FNAB for evaluating this neck mass (11,(30)(31)(32). In the absence of hypercalcemia, the pre-operative parathyroid origin of the neck lump cannot be established.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Examina- 5) [7]. New studies with CE-US and texture analysis are being done but their effectiveness is debatable.…”
Section: Ultrasonographymentioning
confidence: 99%